Solvent-free synthesis of thiobarbituric acids using amberlyst-15 as a green catalyst - Dhonde, Madhukar G.; Gajbhiye, Jayant M.; Katiya, Manish M. (Current Green Chemistry, 2017)

Synthesis of deuterated isopentyl pyrophosphates for chemo-enzymatic labelling methods: GC-EI-MS based 1,2-hydride shift in epicedrol biosynthesis - Said, Madhukar S.; Navale, Govinda R.; Gajbhiye, Jayant M.; Shinde, Sandip S. (RSC Advances, 2019)
A sesquiterpene epicedrol cyclase mechanism was elucidated based on the gas chromatography coupled to electron impact mass spectrometry fragmentation data of deuterated (H-2) epicedrol analogues. The chemo-enzymatic method was applied for the specific synthesis of 8-position labelled farnesyl pyrophosphate and epicedrol. EI-MS fragmentation ions compared with non-labelled and isotopic mass shift fragments suggest that the H-2 of C6 migrates to the C7 position during the cyclization mechanism.

Synthesis of deuterated isopentyl pyrophosphates for chemo-enzymatic labelling methods: GC-EI-MS based 1,2-hydride shift in epicedrol biosynthesis (Retraction of Vol 9, Pg 28258, 2019) - Said, Madhukar S.; Navale, Govinda R.; Gajbhiye, Jayant M.; Shinde, Sandip S. (RSC Advances, 2020)
Retraction of `Synthesis of deuterated isopentyl pyrophosphates for chemo-enzymatic labelling methods: GC-EI-MS based 1,2-hydride shift in epicedrol biosynthesis' by Madhukar S. Said et al., RSC Adv., 2019, 9, 28258-28261.

Synthesis of pyrazole and 1,3,4-oxadiazole derivatives of pharmaceutical potential - Kadam, Mayur; Jadhao, Nitin L.; Gajbhiye, Jayant M. (Prospects in Pharmaceutical Sciences, 2024)
Heterocyclic compounds are important molecules that serve as scaffolds or linkers for the core structure of numerous drug substances. In particular, pyrazole and 1,3,4-oxadiazole are compounds of great interest due to their comprehensive biological activities and interesting structural features. Here, we described an efficient and economical synthetic route leading to N-phenyl substituted pyrazole and 1,3,4-oxadiazole derivatives. Retrosynthetic disconnective analysis showed that the N-phenyl substituted pyrazole can be obtained from chalcone, accessible from the respective aldehyde, and acetophenone. The disubstituted 1,3,4-oxadiazole can be constructed from the respective aldehyde, which originates from pyrrole-containing compound, and formyl chloride. Based on our retrosynthetic analysis, N-phenyl substituted pyrazole was obtained by cyclization of the respective chalcone with phenylhydrazine to give pyrazoline which was in turn converted into pyrazole by oxidative aromatization. Potassium carbonate and a catalytic amount of molecular iodine were used to oxidatively cyclize semicarbazones into 1,3,4-oxadiazoles in a transition metal-free process. Novel pyrazole and 1,3,4-oxadiazoles with potential biological activity are investigated as antituberculosis, anticonvulsant, antidiabetic, anticancer, and tyrosinase inhibitory agents.

Synthesized novel chromogenic reagent and sensor: detection and identification of dichlorvos - Gedam, Ashwin D.; Katiya, Manish M.; Dhonde, Madhukar G.; Ganorkar, Kapil S.; Thakare, Vijay J.; Mandlik, Prashant R.; Jadhao, Nitin L.; Gajbhiye, Jayant M.; Kumar, Ravi; Vaval, Nayana (Heliyon, 2024)
We developed a novel chromogenic reagent and sensor by selective approach, for the detection and identification of dichlorvos, which we tested with the thin layer chromatography method. For the first time, we reported in situ-generated glyoxal as a hydrolysis product, which then interacts with isoniazid to produce a yellow-colored cyclic compound. We used well-known spectroscopic techniques to confirm the chemical identity of the final product. We initially investigated the reaction using a variety of approaches, followed by attempts to establish the reaction mechanism using Density Functional Theory by Gaussian software.
Keywords: DFT analysis; Dichlorvos; Gloyxal; Hydrazone; Isoniazid